Chromosome Abnormalities in Turkish Men with Primary Infertility - Güngör, Tayfun; Kanat Pektaş, Mine; Günel, Müfit; Mollamahmutoğlu, Leyla (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: The present study aims to identify the prevalence and types of chromosome anomalies among Turkish men with primary infertility. STUDY DESIGN: A case-control study was undertaken in 474 Turkish men with primary infertility and 450 phenotypically normal fertile men selected for the control group. RESULTS: Azoospermia is defined to be the most frequent spermiogram abnormality within infertile men, followed by oligoasthenoteratozoospermia. Chromosomal abnormalities were demonstrated to occur significantly more in azoospermic subjects (28.3%) compared to other infertile subjects (11.5%) and fertile men (0.8%). Klinefelter syndrome was detected to be the most frequent chromosomal abnormality with an overall rate of 10.5%. Azoospermia Factor (AZF) microdeletions occur statistically similar among azoospermic men (4.2%) and other infertile men (2.3%), with a total frequency of 3.2%. CONCLUSION: The high rate of chromosomal anomalies among infertile Turkish men strongly suggests the need for routine cytogenetic analysis prior to the application of assisted reproduction techniques.